SPECIFIC SPEED EFFECT ON FRANCIS RUNNER RELIABILITY UNDER VARIOUS OPERATING CONDITIONS - Coutu, André; Monette, Christine; Nennemann, Bernd; Chamberland-Lauzon, Joël; Ruchonnet, Nicolas; Taruffi, Adrien; Straatmann, Richard (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Energy market deregulation and arrival of new players, such as solar and wind turbines, led to an increasing demand for flexible operation of hydraulic urbines. Instead of continuous close to peak operation, it is nowadays not uncommon to see turbines being operated over the whole range, with many start/stops, extensive low load operation, synchronous condenser mode and power/frequency regulation. This new way to operate the units, however, does not come without cost on the machine life expectancy due to the increased number of high and low amplitude cycles introduced in the operation of the unit. To assess machine reliability, it therefore be-comes critical for the owner to understand the real effects of these dynamic phenomena. The purpose of this paper is to show how dynamic phenomena occurring at various operating conditions may affect the lifetime expectancy of different specific speed Francis runners. Runner blade strain gage and pressure site measurements, performed at various locations, and correlated to Computational Fluid Dynamics (CFD) results and structural Finite Element Analysis (FEA) using Fluid Structure Interaction (FSI) techniques, are used to discuss these dynamic phenomena.